Internal peroxy singlet oxygen carrier molecules capable of being quickly converted and application of internal peroxy singlet oxygen carrier molecules

By designing fluoride ion-responsive internal peroxygen singlet oxygen carrier molecules combined with ferrotetraoxide nanomaterials, singlet oxygen release is achieved stably stored at room temperature and controlled by chemical stimulation and magnetic field, which solves the problems of light source and oxygen dependence and thermodynamic instability in the prior art, and realizes controlled release and selective oxidation in a wide temperature zone.

CN120504687APending Publication Date: 2025-08-19DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510500244.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-21
Publication Date
2025-08-19

AI Technical Summary

Technical Problem

The existing singlet oxygen generation system relies on light sources and oxygen, and has environmental sensitivity limitations. Free radical chain reactions lead to accumulation of by-products, and the thermodynamic instability of the internal peroxide precursor, making it difficult to achieve controllable release in a wide temperature zone.

Method used

A class of fluoride ion-responsive internal peroxy singlet oxygen carrier molecules are designed. By loading on ferromagnetic nanomaterials, the chemical reaction triggered by fluoride ions is rapidly converted into internal peroxide to release singlet oxygen at room temperature, and combined with magnetic field control, it achieves space-time and controlled release.

Benefits of technology

It accurately regulates the release of singlet oxygen under light-free conditions, breaks through the environmental sensitivity limitations of traditional photosensitizers, has high thermal stability and time-space controllability, and is suitable for selective oxidation of organic synthesis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120504687A_ABST
    Figure CN120504687A_ABST
Patent Text Reader

Abstract

The invention discloses internal peroxide singlet oxygen carrier molecules capable of being quickly converted and application thereof, and belongs to the field of functional molecule design and intelligent materials. The molecules are functionalized on the ferroferric oxide magnetic nano material, and a singlet oxygen storage system which is kept inert under the normal temperature condition is successfully constructed. When the system is in contact with fluorine ion sources such as tetrabutylammonium fluoride and the like, carbon-silicon bonds are triggered to break through nucleophilic substitution reaction, so that a molecular structure is promoted to be quickly converted into 1, 4-dimethylnaphthalene endoperoxide and is subjected to ring cracking, singlet oxygen is released, and accurate regulation and control of a molecular switch are realized. A DPBF probe verifies that singlet oxygen release of the system can be controlled through fluorine ions, and excellent time-space controllability is shown. Furthermore, a magnetically-controlled singlet oxygen source is constructed by loading on a ferroferric oxide nano-carrier, and a singlet oxygen nano-carrier controlled by a magnetic field is constructed; the limitation that a traditional photosensitizer depends on an external light source and oxygen is broken through, and wide application prospects are achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of functional molecular design and intelligent materials, and specifically relates to a type of fluoride ion responsive singlet oxygen ( ) Design, synthesis and application of carrier molecules in the functionalization of nanomaterials. Background Art

[0002] Singlet oxygen ( As an important member of highly reactive oxygen species (ROS), it has shown significant advantages in the field of organic synthesis due to its unique spin electronic state and selective oxidation properties. Its typical reaction pathway includes: constructing endoperoxide intermediates with olefins through [4+2] cycloaddition reaction, and achieving highly selective transformations such as thioether→sulfoxide, indole→ketone derivatives. However, existing The generation system has three technical bottlenecks: i) dependence on light source and oxygen; ii) accumulation of byproducts caused by free radical chain reaction; iii) thermodynamic instability of endoperoxide precursors. These inherent defects seriously restrict Expanding its application in precision organic transformations such as asymmetric catalysis and multi-step continuous synthesis.

[0003] The current mainstream The generation technology is based on the energy transfer mechanism mediated by photosensitizers (methylene blue / rose bengal, etc.). This system has the following essential limitations: First, the photodynamic control defect - The generation rate and concentration gradient of sulfoxide are directly subject to the irradiation intensity and wavelength parameters, which makes it difficult to apply to scenes without light and oxygen deficiency. Secondly, the interference of photochemical side reactions - especially in the sulfide oxidation system, uncontrollable free radical chain reaction can easily lead to an imbalance in the ratio of sulfoxide / sulfone products (typical selectivity deviation>30%). Moreover, although the traditional peroxide carrier (naphthalene / anthracene / pyridone derivative system) can be released by thermal decomposition, the sulfoxide / sulfone product ratio is not stable. However, its practical application is subject to two limitations: at the thermodynamic level, the Arrhenius decomposition mechanism leads to excessive temperature sensitivity, making it difficult to achieve controlled release in a wide temperature range (-20°C to 100°C); at the stability level, the half-life of most endoperoxides at 298K is less than 72 hours, requiring low-temperature storage (-20°C) and frequent regeneration, which significantly increases operating costs. Summary of the Invention

[0004] Based on the reversible release of singlet oxygen by endoperoxide compounds, the present invention designs a highly thermally stable and rapidly convertible endoperoxide singlet oxygen carrier molecule. This molecule is highly stable at room temperature and can be stored for long periods of time. Upon addition of fluoride ions, the carrier molecule rapidly converts to an unstable endoperoxide molecule by disrupting the disilacyclic ring structure within the molecule. This structure then undergoes a rapid reverse cyclization reaction to release singlet oxygen, achieving the goal of controlled release of singlet oxygen from fluoride ions. The reaction conditions are mild. Furthermore, by loading the molecule onto a magnetic nanomaterial called ferroferric oxide, a magnetic field can be used to control the singlet oxygen source.

[0005] The technical solution of the present invention: a class of compounds having the structure of formula (1):

[0006]

[0007] wherein R1 and R4 are each independently selected from hydrogen, hydroxyl, trimethylsilyl, amino, alkenyl having 2 to 6 carbon atoms, alkynyl having 2 to 6 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkylamino having 1 to 6 carbon atoms, alkoxyalkyl having 2 to 6 carbon atoms, alkyl having 1 to 10 carbon atoms, trifluoromethyl, halogen, alkoxycarbonyl having 2 to 6 carbon atoms, aryl having 6 to 14 carbon atoms, cycloalkyl having 3 to 10 carbon atoms, or ;

[0008] R2 and R3 are each independently selected from hydrogen, hydroxy, trimethylsilyl, amino, alkenyl having 2 to 6 carbon atoms, alkynyl having 2 to 6 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkylamino having 1 to 6 carbon atoms, alkoxyalkyl having 2 to 6 carbon atoms, alkyl having 1 to 10 carbon atoms, trifluoromethyl, halogen, alkoxycarbonyl having 2 to 6 carbon atoms, aryl having 6 to 14 carbon atoms, or ; or R2 and R3 are cycloalkyl groups having 3 to 10 carbon atoms or 3 to 10 membered epoxy groups;

[0009] Wherein, x is an integer from 1 to 2000.

[0010] Furthermore, R1 and R4 are each independently selected from hydrogen, an alkoxy group having 1 to 2 carbon atoms, an alkoxyalkyl group having 2 to 6 carbon atoms, an alkyl group having 1 to 10 carbon atoms, and a trifluoromethyl group;

[0011] R2 and R3 are each independently selected from hydrogen, an alkoxy group having 1 to 2 carbon atoms, an alkoxyalkyl group having 2 to 6 carbon atoms, an alkyl group having 1 to 10 carbon atoms, a halogen group, and an amino group; or R2 and R3 are 3-10 membered epoxy groups.

[0012] Furthermore, R1 and R4 are each independently hydrogen or an alkyl group having 1 to 6 carbon atoms, and R2 and R3 are each independently selected from hydrogen, an alkyl group having 1 to 6 carbon atoms, halogen, and amino; or R2 and R3 are 3-10 membered epoxy groups.

[0013] Furthermore, R1 and R4 are hydrogen, R2 and R3 are independently selected from hydrogen, alkyl with 1-6 carbon atoms, halogen, amino; or R2 and R3 are 3-10 membered epoxy groups.

[0014] A functionalized nano material is prepared by using the above compound.

[0015] Furthermore, the nanomaterial is prepared by using surface-modified nanoparticles and compounds with connecting groups.

[0016] The general structural formula of the compound with a linking group is:

[0017] ;

[0018] Wherein, R1 and R4 are hydrogen, and R2 is selected from hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, and an amino group.

[0019] Furthermore, the surface-modified nanoparticles are iron oxide nanoparticles coated with silica via ethyl silicate and poly(ethylene oxide) nonylphenyl ether, and then reacted with 3-aminopropyltriethoxysilane, NHS-PEG1000-NHS, N-Boc-ethylenediamine, and trifluoroacetic acid in sequence to obtain surface-modified nanoparticles.

[0020] Use of the above-mentioned compound or a pharmaceutically acceptable salt thereof in the preparation of a singlet oxygen-releasing material.

[0021] The application of the above-mentioned nanomaterials in the preparation of singlet oxygen releasing materials.

[0022] The present invention has the following beneficial effects: A highly thermally stable endoperoxide, capable of releasing singlet oxygen under the action of fluoride ions, was designed and synthesized. This endoperoxide was then functionalized and incorporated into a magnetic nanomaterial to develop a smart material capable of controlled release of singlet oxygen by fluoride ions. This smart molecule and material is highly stable at room temperature and does not release singlet oxygen. However, upon addition of fluoride ions, it rapidly releases singlet oxygen, which can be aggregated and separated using a magnetic field. This material can be used for selective oxidation in organic synthesis. This invention successfully establishes a smart material system for controlled singlet oxygen release by fluoride ions, which has broad application prospects.

[0023] This molecule, based on a 1,1,4,4,5,10-hexamethyl-1,2,3,4,5,10-hexahydro-5,10-bridged dihydronaphtho[2,3-b][1,4]disilacyclic ring as its core structure, is functionalized onto a magnetic ferroferric oxide nanomaterial, successfully constructing a singlet oxygen storage system that remains inert at room temperature. Upon contact with a fluoride ion source such as tetrabutylammonium fluoride, this system triggers a nucleophilic substitution reaction that breaks the carbon-silicon bond, rapidly converting the molecular structure to 1,4-dimethylnaphthalene endoperoxide and undergoing ring cleavage, releasing singlet oxygen and achieving precise control of the molecular switch. Verification with a DPBF probe demonstrated that singlet oxygen release from this system can be controlled by fluoride ions, demonstrating excellent temporal and spatial controllability. Furthermore, a magnetically manipulated singlet oxygen source was constructed by loading it onto a ferroferric oxide nanocarrier, successfully constructing a magnetically controlled singlet oxygen nanocarrier. The present invention breaks through the limitation of traditional photosensitizers that rely on external light sources and oxygen, and innovatively develops an intelligent singlet oxygen carrier based on mild chemical stimulation response and magnetic field control, which has broad application prospects.

[0024] The present invention proposes to construct a chemical stimulus response type The controlled release system is innovative in the following aspects: i) the creation of a highly thermally stable endoperoxyl-type singlet oxygen carrier molecule, which achieves a room temperature storage half-life t1 / 2 > 2 months through an energy barrier regulation strategy, breaking through the environmental sensitivity limitations of traditional photosensitizers; ii) the establishment of a tetrabutylammonium fluoride (TBAF)-triggered chemical switch mechanism that can be achieved in the absence of light. The triggered rapid release meets the precise on-demand regulation requirements under mild reaction conditions (25°C, avoid light); iii) the system is innovatively coupled with magnetic Fe3O4 nanocarriers, and the cascade control mode of magnetic field-oriented enrichment-chemical stimulation release is realized for the first time. Precise temporal and spatial regulation of release behavior. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is the time-dependent H NMR spectrum of endoperoxide 5 in deuterated DMSO.

[0026] Figure 2 This is the time-dependent H NMR spectrum of the aromatic region of endoperoxide 5 after adding tetrabutylammonium fluoride to deuterated DMSO.

[0027] Figure 3 This is a graph showing the change in UV absorption of endoperoxide 5 and DPBF over time at 25°C.

[0028] Figure 4 This is a graph showing the change in UV absorption of endoperoxide 5 and DPBF over time at 25°C after adding tetrabutylammonium fluoride.

[0029] Figure 5 This is a graph showing the UV absorption changes of magnetic nanomaterials functionalized with endoperoxide 5 and DPBF at 25°C over time after adding tetrabutylammonium fluoride.

[0030] Figure 6 It is functional Visual verification of nanoparticle magnetic field responsiveness: comparison between the homogeneously dispersed state and the magnetically enriched state.

[0031] Figure 7 yes Electron micrograph of nanoparticle 9. DETAILED DESCRIPTION

[0032] The present invention will be described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention, but are not limited thereto, unless otherwise specified.

[0033] A type of naphthobissilyl singlet oxygen carrier molecule has the following structure:

[0034]

[0035] wherein R2 and R3 are each independently selected from hydrogen, hydroxyl, trimethylsilyl, amino, alkenyl having 2 to 6 carbon atoms, alkynyl having 2 to 6 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkylamino having 1 to 6 carbon atoms, alkoxyalkyl having 2 to 6 carbon atoms, alkyl having 1 to 10 carbon atoms, trifluoromethyl, halogen, alkoxycarbonyl having 2 to 6 carbon atoms, aryl having 6 to 14 carbon atoms, cycloalkyl having 3 to 10 carbon atoms, or ; or R2 and R3 are cycloalkyl groups having 3 to 10 carbon atoms or 3 to 10 membered epoxy groups;

[0036] R1 and R4 are each independently selected from hydrogen, hydroxy, trimethylsilyl, amino, alkenyl having 2 to 6 carbon atoms, alkynyl having 2 to 6 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkylamino having 1 to 6 carbon atoms, alkoxyalkyl having 2 to 6 carbon atoms, alkyl having 1 to 10 carbon atoms, trifluoromethyl, halogen, alkoxycarbonyl having 2 to 6 carbon atoms, aryl having 6 to 14 carbon atoms, cycloalkyl having 3 to 10 carbon atoms, or ;

[0037] Wherein, x is an integer from 1 to 1000.

[0038] In some specific naphthobissilyl singlet oxygen carrier molecules, R2 and R3 are independently selected from hydrogen, alkoxy with 1-2 carbon atoms, alkoxyalkyl with 2-6 carbon atoms, alkyl with 1-10 carbon atoms, trifluoromethyl, halogen, and amino. Alternatively, R2 and R3 are cycloalkyl with 3-10 carbon atoms or 3-10 membered epoxy groups.

[0039] R1 and R4 are each independently selected from hydrogen, an alkoxy group having 1 to 2 carbon atoms, an alkoxyalkyl group having 2 to 6 carbon atoms, an alkyl group having 1 to 10 carbon atoms, and a trifluoromethyl group.

[0040] In some specific naphthobissilyl singlet oxygen carrier molecules, R2 and R3 are independently selected from hydrogen, an alkoxy group having 1-2 carbon atoms, an alkyl group having 1-6 carbon atoms, a trifluoromethyl group, an amino group, or a halogen group. Alternatively, R2 and R3 are 3-10 membered epoxy groups.

[0041] R1 and R4 are each independently selected from hydrogen, an alkoxy group having 1 to 2 carbon atoms, an alkyl group having 1 to 6 carbon atoms, and a trifluoromethyl group.

[0042] In some specific naphthobissilyl singlet oxygen carrier molecules, R2 and R3 are independently selected from hydrogen, halogen, amino, and alkyl groups having 1 to 6 carbon atoms; or R2 and R3 are 3-10 membered epoxy groups;

[0043] R1 and R4 are each independently hydrogen or an alkyl group having 1 to 6 carbon atoms.

[0044] In some specific naphthobissilyl heterocyclic singlet oxygen carrier molecules, R1 and R4 are hydrogen; R2 and R3 are hydrogen, amino, halogen, or alkyl with 1 to 6 carbon atoms, or R2 and R3 are 3-10 membered epoxy groups.

[0045] In some specific naphthobissilyl singlet oxygen carrier molecules, R1 and R4 are hydrogen, R2 and R3 are independently hydrogen, methyl, ethyl, propyl, isopropyl, n-butyl, isobutyl, n-pentyl, n-hexyl, amino, halogen, or R2 and R3 are 3-10 membered epoxy groups.

[0046] The application of the naphthobissilyl heterocyclic derivative in the preparation of singlet oxygen releasing materials.

[0047] The naphthobissilyl heterocyclic derivative is used in the preparation of a drug for transporting singlet oxygen to cells, tissues or organs.

[0048] A drug comprising at least one of the naphthobissilyl singlet oxygen carrier molecules described above;

[0049] and / or carrier;

[0050] The carrier is selected from one or more of metal nanocarriers, non-metal nanocarriers, micelles, liposomes, lactose, sucrose, gelatin, hard magnesium sulfate, and stearic acid.

[0051] A specific naphthobissilyl singlet oxygen carrier molecule has the following structure:

[0052] .

[0053] The preparation steps and reaction formula of the naphthobissilyl singlet oxygen carrier molecule of the present invention are as follows:

[0054]

[0055] Under inert gas protection, trimethylethynylsilane, compound 1, and bis(triphenylphosphine)palladium(II) dichloride are heated in an organic solvent for reaction and purified to obtain compound B.

[0056] Under inert gas protection, a mixture of compound B, 1,2-bis(chlorodimethylsilyl)ethane and n-butyllithium is heated in an organic solvent for reaction and purified to obtain compound C.

[0057] Under the protection of inert gas, compound C reacts with a naphthalene lithium reagent, and then dimethyl sulfate is added to capture the reaction intermediate, and compound D is obtained after purification.

[0058] In an oxygen atmosphere, compound D was dissolved in an organic solvent, and a small amount of methylene blue was added. During the reaction, the reaction system was irradiated with 18W, 630 nm red light throughout the reaction to purify the target compound E.

[0059] Wherein, the definitions of R1-R4 are the same as those in the above-mentioned naphthobissilyl heterocyclic singlet oxygen carrier molecular structure.

[0060] The preparation process of functionalized nanomaterials is as follows:

[0061]

[0062] Under an inert gas atmosphere, iron triacetylacetonate, 1,2-hexadecyl glycol, diphenyl ether, oleylamine, and aniline compounds are dissolved in an organic solvent and stirred at high temperature to react to obtain ferrosoferric oxide nanomaterial 9.

[0063] Nanomaterial 9 was added to an ethanol solution of tetraethyl orthosilicate, ammonia water, and poly(oxyethylene) nonylphenyl ether at room temperature, and stirred at room temperature for 12 hours to obtain silica-coated nanomaterial 9s.

[0064] Nanomaterial 9s was added to an ethanol solution of γ-aminopropyltriethoxysilane at room temperature to obtain nanomaterial 10.

[0065] The nanomaterial 10 was added to a solution of N-hydroxysuccinimide-polyethylene glycol-N-hydroxysuccinimide and N,N-diisopropylethylamine in N,N-dimethylformamide, and the mixture was stirred at room temperature for 12 hours to obtain the nanomaterial 11.

[0066] The nanomaterial 11 was added to a solution of N-tert-butyloxycarbonylethylenediamine and N,N-diisopropylethylamine in N,N-dimethylformamide, and reacted at room temperature for 12 hours to obtain the nanomaterial 12.

[0067] Nanomaterial 12 was added to a dichloromethane solution of trifluoroacetic acid and stirred for 5 hours to obtain nanomaterial 13.

[0068] Nanomaterial 13 was added to a dichloromethane solution of compound 5, 1-hydroxybenzotriazole, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride to obtain nanomaterial 14.

[0069] Wherein, the definitions of R1, R2, R3, and R4 are the same as those in the above-mentioned naphthobissilylheterocyclic singlet oxygen carrier molecular structure.

[0070] The specific embodiments of the present invention are described in detail below in conjunction with the technical solutions:

[0071] Example 1: Preparation of Compound 8

[0072]

[0073] Step a: Under nitrogen protection, dichlorobis(triphenylphosphine)palladium(II) [ , 5 mol%] and cuprous iodide (CuI, 10 mol%) were added to anhydrous deoxygenated triethylamine (16 mL) containing 1,2-diiodobenzene (0.6 mL, 4.5 mmol) to form a homogeneous catalytic system. Subsequently, trimethylsilyl acetylene (1.9 mL, 13.5 mmol) was dissolved in a mixture of deoxygenated tetrahydrofuran (2 mL) and triethylamine (2 mL) and slowly added dropwise to the catalytic system via a constant pressure dropping funnel (addition rate: 0.2 mL / min). The reaction system was stirred continuously at room temperature (25 ± 2°C) under a nitrogen atmosphere for 16 h. After completion of the reaction, the mixture was diluted with dichloromethane (20 mL x 3), washed with saturated ammonium chloride (15 mL x 2), and dried over anhydrous sodium sulfate. After removing the solvent by rotary evaporation under reduced pressure, the residue was purified by flash column chromatography (eluent: n-hexane / ethyl acetate = 100:1, v / v) to obtain compound 2 as a light yellow oil with a yield of 90% (1.1 g).

[0074] Step b: Dissolve compound 2 (541 mg, 2 mmol) in anhydrous tetrahydrofuran (THF, 15 mL) and slowly add n-butyllithium (n-BuLi) solution dropwise in an ice-water bath under nitrogen protection. After stirring at 0°C for 4 hours, slowly add 1,2-bis(chlorodimethylsilyl)ethane dropwise to the reaction system. After the addition is complete, the reaction system is allowed to warm to room temperature and stirred for 12 hours. Add saturated ammonium chloride ( ) aqueous solution to quench the reaction, extract with ethyl acetate (3 × 20 mL), combine the organic phases and wash with anhydrous sodium sulfate ( The solvent was removed under reduced pressure on a rotary evaporator to obtain a crude product, which was then purified by flash chromatography (n-hexane:ethyl acetate = 100:1, v / v) to afford compound 3 as a white solid (yield 45%, 240 mg).

[0075] Step c: Naphthalene (0.96 g, 7.5 mmol) and metallic lithium (0.053 g, 7.5 mmol) were dissolved in 15.0 mL of anhydrous tetrahydrofuran (THF) and stirred under nitrogen for 6 hours to obtain a dark green lithium naphthalene (LiNaph) THF solution (concentration 0.5 mmol / mL). The newly prepared LiNaph / THF solution was placed in an ice-water bath and a solution of compound 3 (268.5 mg, 1 mmol) in anhydrous THF (0.5 mL) was slowly added dropwise. After the addition, stirring was continued for 10 minutes, followed by the dropwise addition of dimethyl sulfate (1 mL, 10.5 mmol). The resulting mixture was stirred at room temperature for 6 hours and then cooled in an ice bath with saturated sodium bicarbonate ( The reaction was quenched with a 5% ethanol solution and extracted with ethyl acetate. The combined organic phases were concentrated under reduced pressure to remove the solvent. The residue was crudely separated by column chromatography (n-hexane:ethyl acetate = 100:1, v / v) to afford a white solid mixture of the product and naphthalene (1.2 g). This mixture was used directly in the subsequent step.

[0076] Step d: The mixture (1.2 g) obtained in step c was dissolved in 5 mL of dichloromethane (DCM), and the reaction system was cooled to 0°C. A catalytic amount of methylene blue was added to the solution, and the mixture was stirred at 0°C under an oxygen atmosphere and irradiated with red light (18 W, 625 nm). After completion of the reaction, the solvent was removed under reduced pressure, and the crude product was purified by silica gel column chromatography (n-hexane:ethyl acetate = 50:1, v / v) to obtain compound 5 (120 mg, 36% yield).

[0077] Step e: Compound 5 (110 mg, 0.33 mmol) was dissolved in 3 mL of toluene. The reaction mixture was heated at 110°C for 40 hours. After cooling to room temperature, the solvent was removed under reduced pressure. The crude product was purified by silica gel column chromatography (n-hexane:ethyl acetate = 50:1, v / v) to afford compound 4 (95 mg, 96% yield).

[0078] Step f: (9.9 mg, 0.015 mmol), 4,4'-di-tert-butyl-2,2'-bipyridine (8.0 mg, 0.03 mmol), bispinacolatodiborane (83.7 mg, 0.33 mmol), and compound 4 (89.5 mg, 0.3 mmol) were mixed in cyclohexane (3 mL) and heated at 80°C for 18 hours. After cooling to room temperature, the solvent was removed under reduced pressure. The crude product was purified by silica gel column chromatography (n-hexane:ethyl acetate = 50:1, v / v) to obtain compound 6 (90 mg, 73% yield).

[0079] Step g: Mix potassium phosphate (1.06 g, 5 mmol), 4-iodobenzoic acid (60 mg, 0.24 mmol), 1,4-dioxane (2 mL) and water (0.5 mL) and stir at room temperature. After argon replacement, add The reaction mixture was heated to 80°C and refluxed under a nitrogen atmosphere for 5 hours. After completion of the reaction, the mixture was cooled to room temperature, acidified with dilute hydrochloric acid, and extracted with ethyl acetate (EtOAc, 3 × 20 mL). The mixture was washed sequentially with water (3 × 20 mL) and saturated sodium chloride solution (3 × 20 mL). The organic phase was dried over anhydrous sodium sulfate, and the solvent was removed under reduced pressure. The crude product was purified by silica gel column chromatography (dichloromethane:methanol = 20:1, volume ratio) to afford compound 7 (70 mg, 84% yield).

[0080] Step h: Dissolve compound 7 (50 mg, 0.12 mmol) in 5 mL of dichloromethane (DCM), and cool the reaction system to 0°C. Add a catalytic amount of methylene blue to the solution, and stir the mixture at 0°C under an oxygen atmosphere while irradiating with red light (18 W, 625 nm). After completion of the reaction, remove the solvent under reduced pressure, and purify the crude product by silica gel column chromatography (dichloromethane:methanol = 50:1, volume ratio) to afford compound 8 (45 mg, 83% yield).

[0081] Refer to the above steps, respectively 、 、 、 The following four naphthobissilyl heterocyclic peroxy singlet oxygen carrier molecules can be prepared using four diiodobenzenes as raw materials:

[0082]

[0083] Example 2: Preparation of functionalized nanomaterials

[0084]

[0085] Preparation of Fe3O4 nanomaterials: Iron(III) triacetylacetonate ( , 2 mmol), 1,2-hexadecanediol (10 mmol), oleic acid (6 mmol), oleylamine (6 mmol) and phenyl ether (20 mL) were mixed and magnetically stirred under a nitrogen atmosphere. The mixture was heated to 200 ° C and maintained for 30 minutes, and then the temperature was raised to reflux (265 ° C) under nitrogen protection and the reaction continued for 30 minutes. The heat source was removed and the black-brown mixture was cooled to room temperature. Under ambient conditions, ethanol (40 mL) was added to the mixture, and the iron oxide nanoparticles were collected by a neodymium magnet and washed three times with deionized water and ethanol. Finally, the iron oxide nanoparticles 9 were dried under an argon atmosphere for subsequent functionalization treatment. The electron microscope photo of the iron oxide nanoparticles 9 is shown in FIG. Figure 7 shown.

[0086] Step i: Add ethanol (6 mL) to a 100 mL reaction flask and continue stirring. Slowly add IGPEAL [poly(oxyethylene) nonylphenyl ether] (1.4 mL) to the solution over 5 minutes. Then, add iron oxide nanoparticles (60 mg) suspended in ethanol (6 mL) dropwise to the mixture. After the addition, sonicate the mixture at room temperature for 5 minutes and then stir vigorously for 15 minutes. Add ammonia solution (25%) The reaction mixture was stirred for 30 minutes. Tetraethyl orthosilicate (TEOS, 248 μL, 232 mg, 1.1 mmol) was then added. The final mixture was sonicated for 30 minutes and stirred at room temperature for 12 hours. The silica-coated iron oxide nanoparticles were separated using a neodymium magnet, washed three times with water and three times with DMF, and finally dried under an argon atmosphere.

[0087] Step j: 80 mg of silica-coated iron oxide nanoparticles were dispersed in ethanol (8 mL) and sonicated for 10 minutes. The dispersion was then stirred at room temperature, and (3-aminopropyl)triethoxysilane (APTES, 676 μL, 660 mg, 3 mmol) was added dropwise. The reaction mixture was stirred at room temperature for 12 hours. The nanoparticles were magnetically separated using a neodymium magnet and washed three times with deionized water and three times with dimethylformamide (DMF). Finally, the nanoparticles were dried under an argon atmosphere to obtain functionalized nanoparticles 10.

[0088] Step k: 80 mg of nanoparticles 10 were dispersed in dimethylformamide (DMF, 8 mL) and sonicated for 10 minutes. NHS-PEG1000-NHS [N-hydroxysuccinimide-polyethylene glycol 1000-N-hydroxysuccinimide] (60 mg, 0.06 mmol) and N,N-diisopropylethylamine (DIPEA, 16 μL) were then added to the suspension, and stirring was continued at room temperature for 12 hours. After the reaction was complete, the suspension was washed three times with DMF and finally dried under an argon atmosphere to obtain surface-modified nanoparticles 11.

[0089] Step 1: N-Boc-ethylenediamine (19.2 mg, 0.12 mmol) was added to a dispersion of the nanoparticles (80 mg) in dimethylformamide (DMF, 8 mL) and stirred at room temperature for 12 hours. After the reaction, the functionalized nanoparticles were washed three times with DMF and three times with dichloromethane (DCM), and finally dried under an argon stream to obtain surface-modified nanoparticles 12.

[0090] Step m: Trifluoroacetic acid (19.2 mg, 1.2 mmol) was added to a dichloromethane (DCM, 8 mL) dispersion of the nanoparticles (80 mg) and stirred at room temperature for 12 hours. After the reaction, the functionalized nanoparticles were washed three times with DMF and three times with dichloromethane (DCM), and finally dried under an argon stream to obtain surface-modified nanoparticles 13.

[0091] Step n: EDCI (4.2 mg, 0.022 mmol) and HOBt (3 mg, 0.022 mmol) were added to a mixture of compound 8 (9 mg, 0.02 mmol) and nanoparticles 13 (80 mg) in anhydrous dichloromethane (10 mL). After the reaction was complete, the functionalized nanoparticles were washed three times with water, ethanol (EtOH), and dichloromethane (DCM), followed by drying under an argon stream to obtain surface-modified nanoparticles 14.

[0092] Example 3

[0093] To verify the stability of endoperoxide 5, endoperoxide 5 was dissolved in deuterated dimethyl sulfoxide (DMSO-d6) for H NMR spectroscopy and stored at room temperature (25°C) for two months between the two tests. Figure 1 The following is the H NMR spectrum of compound 5 in deuterated dimethyl sulfoxide (DMSO-d6) at 25 ° C. Figure 1 :0 months; spectrum Figure 2 : 2 months). As can be seen from the NMR spectrum, the chemical shift of the hydrogen atoms in the endoperoxide 5 molecule did not change, so the structure of compound 5 did not change significantly during the storage period of up to two months, showing good stability.

[0094] Example 4

[0095] Experiment on the reaction of endoperoxide 5 with tetrabutylammonium fluoride. Endoperoxide 5 was dissolved in deuterated dimethyl sulfoxide, tetrabutylammonium fluoride was added to the NMR tube, and the NMR hydrogen spectrum of the system was measured at room temperature over time. The specific changes are as follows: Figure 2 As shown, the spectrum Figure 1 :0 hours; spectrum Figure 2 : 2 hours; score Figure 3 : 4 hours; score Figure 4 : 6 hours; score Figure 5 : 8 hours; score Figure 6 : 12 hours; spectrum Figure 7 : 24 hours. In the ¹H NMR spectrum shown, changes in the peaks attributed to 1,4-dimethylnaphthalene (8.02-7.99, 7.58-7.55, and 7.24 ppm) reflect the ring inversion reaction of the naphthalene-terminated peroxide. Upon treatment with tetrabutylammonium fluoride (TBAF), a peak at 6.73 ppm rapidly appeared, indicating that compound 5 reacted with fluoride ions to form the 1,4-dimethylnaphthalene-terminated peroxide. As the intensity of the characteristic peaks of the parent naphthalene increased, the intensities of the peaks corresponding to the 1,4-dimethylnaphthalene-terminated peroxide (7.36-7.33, 7.27-7.24, and 6.73 ppm) gradually decreased.

[0096] Example 5

[0097] Release of singlet oxygen from endoperoxide 5 ( ) experiment, the experiment selected 1,3-diphenylisobenzofuran (DPBF) as the selective The capture agent was studied in N,N-dimethylformamide (DMF). The specific method is as follows: First, a DMF reaction mixture containing 500 μM compound 5 and 50 μM DPBF was prepared. Time course monitoring was performed at room temperature (25°C) in the dark, and spectral data were collected every 10 minutes. Figure 3The figure shows the UV absorption changes of endoperoxide 5 and DPBF over time at 25°C. Between 80 and 90 minutes, solid tetrabutylammonium fluoride (TBAF) was added to the cuvette to a final concentration of 30 mM in the solution. Figure 4 This is a graph showing the change in UV absorption of endoperoxide 5 and DPBF at 25°C over time after adding tetrabutylammonium fluoride. By monitoring the characteristic change in absorbance at λmax = 414 nm over time, the The fluoride-mediated decomposition of DPBF, its signal decay kinetics and the fluoride-induced desilylation reaction and subsequent Release process association.

[0098] Example 6

[0099] Functionalized nanomaterials release singlet oxygen ( To evaluate the ability of functionalized nanoparticles 14 to generate and store singlet oxygen in dimethylformamide (DMF), ) capacity, the commercial singlet oxygen scavenger 1,3-diphenylisobenzofuran (DPBF) was used. After adding tetrabutylammonium fluoride (TBAF), UV-visible absorption spectroscopy (UV-vis) measurements were performed every 30 minutes. Figure 5 The following is a graph showing the UV absorption changes over time at 25°C of a magnetic nanomaterial functionalized with endoperoxide 5 and DPBF after the addition of tetrabutylammonium fluoride. To avoid interference from the iron oxide nanomaterial's own absorbance, the sample cuvette was placed on a neodymium magnet for 15 minutes before each spectral measurement to allow the magnetic nanomaterial to fully settle to the bottom of the cuvette before absorbance measurement.

[0100] Example 7

[0101] Verification experiment of the adsorption performance of magnetic field-driven functionalized Fe3O4 nanomaterials. 30 mg of surface-functionalized Fe3O4 nanoparticles 14 were accurately weighed and dispersed in 15 mL of N,N-dimethylformamide (DMF) solvent. After 10 minutes of ultrasonic dispersion treatment, a uniform and stable suspension was formed ( Figure 6 a). Then, a magnetic response test was carried out under the action of an external strong magnet. After 15 minutes, a significant magnetic phase separation phenomenon was observed: Figure 6 As shown in Figure b, the reaction system transforms from an initial homogeneous suspension into a nearly colorless, transparent solution, while the functionalized nanoparticles accumulate on the inner wall of the glass container near the magnet. This experimental phenomenon directly demonstrates the excellent magnetic field response characteristics of the functionalized nanoparticles and their controllable aggregation behavior under external field.

[0102] The above embodiments are only used to illustrate the present invention. Any equivalent transformations and improvements based on the technical solution of the present invention should not be excluded from the protection scope of the present invention.

Claims

1. A compound characterized in that It has the structure of formula (1): ; wherein R1 and R4 are each independently selected from hydrogen, hydroxyl, trimethylsilyl, amino, alkenyl having 2 to 6 carbon atoms, alkynyl having 2 to 6 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkylamino having 1 to 6 carbon atoms, alkoxyalkyl having 2 to 6 carbon atoms, alkyl having 1 to 10 carbon atoms, trifluoromethyl, halogen, alkoxycarbonyl having 2 to 6 carbon atoms, aryl having 6 to 14 carbon atoms, cycloalkyl having 3 to 10 carbon atoms, or ; R2 and R3 are each independently selected from hydrogen, hydroxy, trimethylsilyl, amino, alkenyl having 2 to 6 carbon atoms, alkynyl having 2 to 6 carbon atoms, alkoxy having 1 to 5 carbon atoms, alkylamino having 1 to 6 carbon atoms, alkoxyalkyl having 2 to 6 carbon atoms, alkyl having 1 to 10 carbon atoms, trifluoromethyl, halogen, alkoxycarbonyl having 2 to 6 carbon atoms, aryl having 6 to 14 carbon atoms, or ; or R2 and R3 are cycloalkyl groups having 3 to 10 carbon atoms or 3 to 10 membered epoxy groups; Wherein, x is an integer from 1 to 2000.

2. The compound according to claim 1, characterized in that R1 and R4 are each independently selected from hydrogen, an alkoxy group having 1 to 2 carbon atoms, an alkoxyalkyl group having 2 to 6 carbon atoms, an alkyl group having 1 to 10 carbon atoms, and a trifluoromethyl group; R2 and R3 are each independently selected from hydrogen, an alkoxy group having 1 to 2 carbon atoms, an alkoxyalkyl group having 2 to 6 carbon atoms, an alkyl group having 1 to 10 carbon atoms, a halogen group, and an amino group; or R2 and R3 are 3-10 membered epoxy groups.

3. The compound according to claim 1, characterized in that R1 and R4 are each independently hydrogen or an alkyl group having 1 to 6 carbon atoms, and R2 and R3 are each independently selected from hydrogen, an alkyl group having 1 to 6 carbon atoms, halogen, and amino; or R2 and R3 are 3-10 membered epoxy groups.

4. The compound according to claim 1, characterized in that R1 and R4 are hydrogen, R2 and R3 are independently selected from hydrogen, alkyl with 1 to 6 carbon atoms, halogen, and amino; or R2 and R3 are 3-10 membered epoxy groups.

5. A functionalized nanomaterial, characterized in that: The nanomaterial is prepared by using the compound described in any one of claims 1-4.

6. The nanomaterial according to claim 5, characterized in that: The nanomaterial is prepared by using surface-modified nanoparticles and compounds with connecting groups. The general structural formula of the compound with a linking group is: ; Wherein, R1 and R4 are hydrogen, and R2 is selected from hydrogen, an alkyl group having 1 to 6 carbon atoms, a halogen, and an amino group.

7. The nanomaterial according to claim 6, characterized in that: The surface-modified nanoparticles are iron oxide nanoparticles that are coated with silica via ethyl silicate and poly(ethylene oxide) nonylphenyl ether, and then reacted with 3-aminopropyltriethoxysilane, NHS-PEG1000-NHS, N-Boc-ethylenediamine, and trifluoroacetic acid in sequence to obtain surface-modified nanoparticles.

8. Use of the compound according to any one of claims 1 to 4 or a pharmaceutically acceptable salt thereof in the preparation of a singlet oxygen-releasing material.

9. Use of the nanomaterial according to any one of claims 5 to 7 in preparing a material that releases singlet oxygen.